HUBUNGAN FAKTOR STRATEGI PROMOSI KESEHATAN TERHADAP TINGKAT PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA TATANAN RUMAH TANGGA DI PUSKESMAS BISSAPPU KABUPATEN BANTAENG - Andi Asliana Sainal; Murni (Universitas Pahlawan Tuanku Tambusai, 2022)
Health promotion is a process that supports people to improve their own health control. Clean and healthy living behavior is essentially the basis of prevention that every individual and society can do to prevent the occurrence of disease. The level of PHBS in the household setting is influenced by the health promotion strategy (advocacy, condition development and community empowerment). The type of research used is Observational analytic with a Cross Sectional Study design. The study population was all heads of families in the work area of ??the Bissappu Health Center, Bantaeng Regency. The research sample was 60 respondents using purposive sampling. Data analysis using Chi Square test. The univariate results showed that 63.3% of the respondents had poor PHBS level, based on the health promotion strategy, the advocacy variable was in the less category of 55.0%, condition development variable in the less category of 40% and the community empowerment variable in the less category of 43%. The results of Chi-Square test, it was found that there a significant relationship between health promotion strategies, advocacy (p-value = 0.007 < ? 0,05), condition development (p-value = 0,003 < ? 0,05 and community empowerment (p-value = 0,017 < ? 0,05) with PHBS level. The conclusion of this research is a significant relationship between the factors of health promotion strategies (advocacy, condition development and community empowerment) on the level of Clean and Healthy Life Behavior (PHBS) in household arrangements at the Bissappu Health Center, Bantaeng Regency. It is recommended that all parties (government, community leaders, religious leaders and related parties) be more proactive in implementing the PHBS program. It is hoped that the Puskesmas can implement a health promotion strategy according to the government's target in realizing the Indonesian people to carry out PHBS well in order to achieve health level IV.